2008
DOI: 10.1016/j.jmb.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

On the Evolution of the tRNA-Dependent Amidotransferases, GatCAB and GatDE

Abstract: SummaryGlutaminyl-tRNA synthetase and asparaginyl-tRNA synthetase evolved from glutamyl-tRNA synthetase and aspartyl-tRNA synthetase, respectively, after the split in the last universal communal ancestor (LUCA). Glutaminyl-tRNA Gln and asparaginyl-tRNA Asn were likely formed in LUCA by amidation of the mischarged species, glutamyl-tRNA Gln and aspartyl-tRNA Asn , by tRNA-dependent amidotransferases as is still the case in most bacteria and all known archaea. The amidotransferase GatCAB is found in both domains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 69 publications
(52 reference statements)
5
88
0
1
Order By: Relevance
“…In keeping with the prediction that all archaeal GluRSs are nondiscriminating (32), the acceptor stem loop is indeed absent from all archaea, with only one exception. The Sulfolobus solfataricus GluRS has a similar loop (Fig.…”
Section: Thermautotrohpicussupporting
confidence: 76%
“…In keeping with the prediction that all archaeal GluRSs are nondiscriminating (32), the acceptor stem loop is indeed absent from all archaea, with only one exception. The Sulfolobus solfataricus GluRS has a similar loop (Fig.…”
Section: Thermautotrohpicussupporting
confidence: 76%
“…In archaea, GatCAB is used only for Asn-tRNA Asn formation as GatDE forms Gln-tRNA Gln (16,17). Both AdTs likely were present in early archaea (40). The specificity of archaeal GatCAB for Asn-tRNA Asn synthesis might have enabled archaeal AspRS to coevolve with the AdT to form a thermostable complex in which GatCAB is not released following Asn-tRNA Asn synthesis.…”
Section: Sepcyse and Trnamentioning
confidence: 99%
“…Early bacteria likely emerged from the last universal common ancestral state (LUCAS) with just one AdT-GatCAB-for both Gln-tRNA Gln and Asn-tRNA Asn formation (40). After AsntRNA Asn formation in early bacteria, the release of GatCAB from bacterial ND-AspRS might be have been beneficial, because the free GatCAB could easily be repurposed for GlntRNA Gln formation with GluRS.…”
Section: Sepcyse and Trnamentioning
confidence: 99%
“…We analyzed the phylogeny of GatB because this subunit is restricted to AdTs. The analysis showed that both GatBo and GatB are in the same bacterial clade and are not clustered with the archaeal GatB of the monospecific archaeal GatCAB AdTs (45). As a result, both GatCABs, GatCABo and GatCAB, will very likely display the same activities and specificities.…”
Section: Gatcabo Adt Is Able To Generate Both Asn-trna Asn and Gln-trnamentioning
confidence: 96%